{The unexpected function of a highly conserved YXX$Φ$ motif in HCV core protein} - Karamichali, Eirini; Serti, Elisavet; Gianneli, Aikaterini; Papaefthymiou, Aikaterini; Kakkanas, Athanassios; Foka, Pelagia; Seremetakis, Alexandros; Katsarou, Konstantina; Trougakos, Ioannis P.; Georgopoulou, Urania (Infection, Genetics and Evolution, 2017)
Hepatitis C virus (HCV) is an RNA positive strand virus, member of the Flaviviridae family. The HCV viral particle is composed of a capsid containing the genome, surrounded by an endoplasmic reticulum (ER)-derived lipid bilayer where E1 and E2 are assembled as heterodimers. However, different forms of viral particles have been identified in the serum of HCV-infected patients, including non-enveloped particles. Previous reports have demonstrated that HCV non-enveloped capsid-like particles (HCVne) can be generated by HCV core protein sequence. This sequence possesses a highly conserved $Υ$ΧΧ$Φ$ motif and distal di-leucine motifs that confer primary endocytosis signals, enabling HCVne to enter hepatic cells via clathrin-mediated endocytosis. Although HCV core's primary function is to encapsidate the viral genome, it also interacts with a variety of cellular proteins in order to regulate host cell functions such as gene transcription, lipid metabolism, apoptosis and several signaling pathways. In this report, we demonstrate that the YXX$Φ$ motif of HCV core protein is crucial for the architectural integrity of the particulate form of HCVne. Moreover, we show that the YXX$Φ$ motif in the HCV core sequence plays a pivotal role in the signaling events following HCVne clathrin-mediated endocytosis by inducing the AP-2 clathrin adaptor protein, which in turn redirect HCVne trafficking to the lipid droplets (LDs) via the endosomal-lysosomal pathway. HCVne and LDs co-localization affects the HCV life cycle by enhancing viral replication.
Keywords: AP-2M1; HCV core; HCVne; Lipid droplets; Replication; YXX$Φ$ motif